Comparing phasal aspect in some West Chadic and West Benue Congo languages: Inching toward a crosslinguistic West African perspective (Afrika und Übersee, 2025)
We undertake an initial crosslinguistic comparison of formal coding linked to the functions of phasal aspect in selected languages from West Chadic and West Benue Congo. Canonical phasal aspect types are semantically characterized as INITIATION, TERMINATION, and CONTINUATION. We consider phasal and non-phasal forms, the latter having similar positional limitations as phasal aspect expressions. In Hausa and Miya, phasal aspect is coded by verbs and an immediately following complement. Hausa phasal verbs take truncated sentence-complements, gerundives or participles, or sentence-complements, while those in Miya show truncation or parataxis. In the same slot as phasal aspect forms Hausa exhibits verbs that do not convey aspectuality. Instead, they provide either temporal interpretations of various kinds, frequency, duration, habituality, or meanings that are capacitive or quantitative in nature. In Emai of West Benue Congo, phasal aspect is coded by verbs with truncated complements and by grammatical morphemes. The latter code canonical phasal aspect and precede the main verb. In the same pre-verb position, Emai and other West Benue Congo languages exhibit grammatical morphemes that show non-canonical phasal aspect: temporal interpretations as well as capacitive, volitive, or quantitative meanings. We conclude that canonical phasal aspect forms and similarly positioned but non-phasal forms in West Africa provide fertile ground for further crosslinguistic comparison.
Keywords: Phasal aspect; Hausa; Miya; Edoid; Yoruboid; preverbs